On factor structure of the work involvement construct in the Malaysian context / Johanim Johari, Khulida Kirana Yahya and Abdullah Omar - Johari, Johanim; Yahya, Khulida Kirana; Omar, Abdullah (Research Management Institute (RMI), 2012)
Studies have conceptualized work involvement as a multidimensional construct. However researchers have so far provided inconclusive agreement on the dimensionality of this latent factor. Therefore, a re-conceptualization of work involvement scale is crucial due to the inconsistencies in the measure of this construct. This study attempts to examine the construct validity of the work involvement measure by using a Malay-translated version of the instrument. A priori proposition was made that work involvement is a single-dimensional construct. This means that work involvement measurement can be represented by a single factor consisting of five items. SPSS version 14 and AMOS 16 were used to analyze the data. The findings supported the single-dimensionality of work involvement factor based on the results from exploratory and confirmatory factor analyses. The research results also showed acceptable internal consistency reliability for the work involvement factor, which suggested the utility of the five-item work involvement measure in the Malaysian context.